1994
DOI: 10.1007/bf02599175
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate and inappropriate prescribing of narcotics for ambulatory HIV-positive patients

Abstract: Physicians tend to prescribe narcotics inappropriately to patients known to have previously abused drugs and to those who appear wasted or have dementia. Physicians have a duty to prescribe narcotics appropriately as guided by recognized medical indications and the patients' views concerning their current medical needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The association of drug abuse with prescription opioid use is consistent with earlier studies among HIV-infected individuals 8, 29-31 , as well as recent studies comparing prescription opioid use between those with and without substance use disorders in the general population 18, 32 . Those with diagnosed substance use disorders may have reduced pain tolerance 23, 33 , or perhaps increased prevalence of other comorbid illnesses 34 , resulting in more frequent use of prescription opioids at higher dosage levels.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The association of drug abuse with prescription opioid use is consistent with earlier studies among HIV-infected individuals 8, 29-31 , as well as recent studies comparing prescription opioid use between those with and without substance use disorders in the general population 18, 32 . Those with diagnosed substance use disorders may have reduced pain tolerance 23, 33 , or perhaps increased prevalence of other comorbid illnesses 34 , resulting in more frequent use of prescription opioids at higher dosage levels.…”
Section: Discussionsupporting
confidence: 88%
“…Those with a history of drug abuse also persistently reported aberrant opioid use during follow-up. Another study of 190 HIV-infected individuals seen in a single U.S. medical clinic indicated that HIV-infected individuals with a history of IDU were more likely to have been prescribed narcotics inappropriately compared with other men who have sex with men or heterosexuals 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, providers and patients must manage OT in the context of the competing demands of medical, psychiatric and substance use comorbidities, and accordingly, polypharmacy. 7, 14, 18, 30, 38, 42, 46 Moreover, military veterans, in general, suffer from a high prevalence of chronic pain, particularly veterans returning from Afghanistan and Iraq (i.e., Operation Enduring Freedom and Operation Iraqi Freedom, respectively). 46 To date, no studies have examined the provision of OT guideline-concordant care.…”
mentioning
confidence: 99%